2018
DOI: 10.2147/ppa.s176471
|View full text |Cite
|
Sign up to set email alerts
|

A third-party investigation of inpatient satisfaction with a tertiary hospital in People’s Republic of China

Abstract: BackgroundConflicts between doctors and patients occur in People’s Republic of China each year. Serious negative relationships between doctors and patients are a significant social problem. This study aims to evaluate the satisfaction of inpatients in a tertiary hospital through a third party and analyze the relationship between sociodemographic characteristics and overall satisfaction.Patients and methodsA cross-sectional investigation was conducted to obtain the demographic information and results for 20 ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
2
17
3
Order By: Relevance
“…Since age is an unmodified factor, policymakers and organizations may choose to concentrate on enforcement of healthcare policies that supports all age categories [ 35 ]. The total influences of sex and education on satisfaction were not significant, which was inconsistent with studies elsewhere where education level of outpatients were found to affect outpatient satisfaction [ 14 ]. This may be related to the shorter outpatient visit time, shorter communication time with doctors, and higher overall quality of service in large hospitals in our study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Since age is an unmodified factor, policymakers and organizations may choose to concentrate on enforcement of healthcare policies that supports all age categories [ 35 ]. The total influences of sex and education on satisfaction were not significant, which was inconsistent with studies elsewhere where education level of outpatients were found to affect outpatient satisfaction [ 14 ]. This may be related to the shorter outpatient visit time, shorter communication time with doctors, and higher overall quality of service in large hospitals in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…At the providers’ level, factors such as physicians’ clinical experience and hospitals’ environment might affect the outpatients’ perception towards healthcare services provided [ 12 ]. Similarly, outpatient-level factors such as demographic characteristics, motivation, and economic status play an important role in hospital services evaluation [ 13 , 14 ]. One recent study found that the education status, occupation and annual income were significantly associated with overall patient satisfaction [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical doctor-patient relationship in China is facing serious challenges, and an ever-increasing number of conflict events between medical staff and patients have been reported, which triggered increased rates of patient dissatisfaction. [34][35][36][37][38] This study, however, found that "the patience of doctors" and "patients' privacy protection" and "service attitude" showed a relatively high level of satisfaction and a relatively high degree of influence. The findings indicated that outpatient satisfaction with doctors' patience, service attitude and patient privacy protection had gradually improved.…”
Section: Discussionmentioning
confidence: 99%
“…Dental patient satisfaction is one of the important items for evaluating clinical services,14 so understanding and measuring its priority to the treatment appears to be essential for dentists to improve clinical outcomes. Usually, satisfactory patients have better compliance, the same as the rate of follow-up.…”
Section: Discussionmentioning
confidence: 99%